Gender and social targeting in plant breeding - Orr, Alastair; Cox, Cindy M.; Ru, Yating; Ashby, Jacqueline A. (CGIAR System Organization, 2018)
Gender and social targeting can improve the relevance and effectiveness of plant-breeding programs serving resource-poor farmers, traders, processors, and consumers. Generally, these breeding programs have limited information about their clients, which makes it difficult to prioritize breeding objectives. As a result, products from these breeding programs may not meet the needs of their intended users.